MENINGKATKAN INTERAKSI SOSIAL MELALUI PERMAINAN TRADISIONAL BALI - I Made Mahaardhika (Widyadari : Jurnal Pendidikan, 2021)
This study aims to increase students social interaction through Balinese traditional games. The subjects in this study were nine grade IV students of elementary school 2 Jagapati who had low social interaction. To measure the level of student social interaction is the social interaction scale. To improve students' social interaction, researchers applied the traditional Balinese game Juru Pencar as a technique in providing group guidance, so that students can apply aspects of communication, social contact, cooperation and mutual respect and motivation in the play activities they participate in. Group guidance through traditional games is carried out in four activities. The results showed that there was an increase in the increase in students social interaction before and after the traditional scavenger game activities. The pretest results are 288 with an average of 32, while the posttest results are 554 with an average of 62, where the difference is 266, so it can be said that group guidance by applying the traditional Balinese game technique of scattering can increase student social interaction.